القدرات النفس لغوية لدى التلاميذ ذوي صعوبات التعلم وأقرانهم العاديين: دراسة مقارنة - صقر، السيد أحمد محمود; المحلاوي، محمد إبراهيم إبراهيم; زايد، أمل محمد أحمد (جامعة كفر الشيخ - كلية التربية, 2020)
تنتشر صعوبات التعلم بين العديد من التلاميذ، وتختلف خصائص التلاميذ ذوي صعوبات التعلم، عن العاديين، في مظاهر الاستقبال اللغوي، والتعبير اللغوي، لذا أجريت هذه الدراسة من أجل التمييز بين التلاميذ ذوي صعوبات التعلم، والتلاميذ العاديين، وتكونت عينة الدراسة من (26) تلميذ وتلميذة، (14 تلميذ، و12 تلميذة)، من ذوي صعوبات تعلم القراءة، و (٢٦) من العاديين (١٤ تلميذ، و١٢ تلميذة)، وباستخدام بطارية إلينوي للقدرات النفس لغوية، والتي تم بناء اختباراتها في ضوء نموذج "اسجود" والتي تمثل (٩) اختبارات فرعية، تشمل مظاهر الاستقبال اللغوي، والتعبير اللغوي، وهذه الاختبارات هي: اختبار السمع اللفظي الآلي، الترابط السمعي الصوتي، التعبير اللفظي، التسلسل السمعي الصوتي، الترابط البصرى الحركي، الإدراك السمعي، الإدراك البصرى، التعبير بالحركة، التسلسل البصرى الحركي، وهي تقيس مظاهر الاستقبال والتعبير اللغوي، أظهرت النتائج أنه توجد فروق ذات دلالة إحصائية بين متوسطات درجات التلاميذ ذوي صعوبات التعلم (القراءة)، ومتوسطات درجات التلاميذ العاديين في القدرات النفس لغوية لصالح العاديين، في اختبارات السمع اللفظي الآلي، الترابط السمعي الصوتي، التعبير اللفظي، التسلسل السمعي الصوتي، الترابط البصرى الحركي، الإدراك السمعي، وغير دالة إحصائياً على اختبارات الإدراك البصرى، التعبير بالحركة، التسلسل البصرى الحركي، وأيضا توجد فروق ذات دلالة إحصائية بين متوسطات درجات التلاميذ ذوي صعوبات التعلم (القراءة)، ومتوسطات درجات التلاميذ العاديين في المجموع الكلي للاختبارات الفرعية لصالح العاديين.
Learning difficulties are widespread among many students, and the characteristics of pupils with learning difficulties differ from the ordinary ones in the manifestations of linguistic reception and language expression, so this study was conducted in order to distinguish between students with learning difficulties and ordinary students, and the study sample consisted of (26) A male and female student, (14 male and 12 female students), with reading difficulties, and (26) ordinary students (14 male and 12 female students), using the Illinois Self-Linguistic Abilities Battery, whose tests were built in light of the "Asgod" model, which represents (9) Sub-tests, including manifestations of language reception and language expression, and these tests are: Test of automatic verbal hearing, auditory-sound correlation, verbal expression, audio¬-sound sequence, visual-motor correlation, auditory perception, visual perception, movement expression, visual-motor sequence, and it measures the aspects of reception and linguistic expression, the results showed that there are statistically significant differences between Average scores for students with learning difficulties (reading), and average scores for normal students in psycho¬linguistic abilities in favor of the ordinary, in tests of automatic verbal hearing, auditory-sound correlation, verbal expression, auditory-sound sequences, visual-motor correlation, auditory perception, and are not statistically significant on tests Visual perception, movement expression, visual movement sequences, and there are also statistically significant differences between the mean scores of students with Learning difficulties (reading), and the average marks of ordinary students in the total sub-tests in favor of the ordinary
Keywords: صعوبات التعلم -- صعوبات التعلم النمائية -- صعوبات التعلم الأكاديمية -- القدرات النفس لغوية -- الطلبة ذوي صعوبات التعلم